Extranodal NK/T-cell Lymphoma, Nasal Type (Angiocentric T-cell Lymphoma): Laporan Kasus dan Kajian Diagnosis Histopatologik - Prasetyo, Awal; Istiadi, Hermawan; Puspasari, Dik (Majalah Patologi Indonesia, 2023)
Extranodal NK/T-cell lymphoma, nasal type (ENKL) is a lymphoid neoplasm, which in the past has been grouped as a type of granulomatous diseases, is an aggressive non-Hodgkin’s lymphoma. The aggressiveness of ENKL is characterized clinically by nonrelenting destruction of the midline structures of the palate and nasal fossa. The histopathological diagnosis of this disease is difficult to enforced despite the malignant clinical course recognizably because of extensive tissue necrosis and multiple biopsies are often required. ENKL has an ominous prognosis, as the average survival rate is between 6 and 25 months. This case report describes the difficulties in making histopathological diagnosis of a 52-year-old male patient who presented with nasal obstruction and foul smelling, destructive and ulseratif lesion over for 3 months duration, and failed to treat with antibiotics and anti-inflammatories drugs. The diiferential diagnosis of the multiple biopsies was nasal cavity granuloma, NK/T cell lymphoma and Wegener granulomatosis. After immunohistochemical panel analysis of Pansitokeratin (AE1/3), LCA, CD3 and CD56, the patient be confirmed had an ENKL, nasal type which in the past also known as angiocentric T-cell lymphoma.